Litterfall dynamics under different tropical forest restoration strategies in Costa Rica - Celentano, Danielle (2011)
In degraded tropical pastures, active restoration strategies have the potential to facilitate forest regrowth at rates that are faster than natural recovery, enhancing litterfall, and nutrient inputs to the forest floor. We evaluated litterfall and nutrient dynamics under four treatments: plantation (entire area planted), tree islands (planting in six patches of three sizes), control (same age natural regeneration), and young secondary forest (7–9-yr-old natural regeneration). Treatments were established in plots of 5050m at six replicate sites in southern Costa Rica and the annual litterfall production was measured 5 yr after treatment establishment. Planted species included two native timber-producing hardwoods (Terminalia amazonia and Vochysia guatemalensis) interplanted with two N-fixing species (Inga edulis and Erythrina poeppigiana). Litter production was highest in secondary forests (7.3 Mg/ha/yr) and plantations (6.3), intermediate in islands (3.5), and lowest in controls (1.4). Secondary forests had higher input of all nutrients except N when compared with the plantation plots. Inga contributed 70 percent of leaffall in the plantations, demonstrating the influence that one species can have on litter quantity and quality. Although tree islands had lower litterfall rates, they were similar to plantations in inputs of Mg, K, P, Zn, and Mn. Tree islands increased litter production and nutrient inputs more quickly than natural regeneration. In addition to being less resource intensive than conventional plantations, this planting design promotes a more rapid increase in litter diversity and more spatial heterogeneity, which can accelerate the rate of nutrient cycling and facilitate forest recovery.